ALGUNAS REFLEXIONES SOBRE LA SOLUCIÓN DE PROBLEMAS EN LA ESCUELA PRIMARIA: SOME REFLECTIONS ABOUT SOLVING PROBLEMS IN PRIMARY SCHOOLS - Reyes Pérez, Irán Félix; Silva Téllez, Naury; Fernández Chelala, Rosa María (Opuntia Brava, 2018)
En el artículo se exponen algunas consideraciones sobre la enseñanza de la solución de problemas, se abordan los principales factores que la afectan y se ofrecen los elementos básicos a lograr en las etapas de desarrollo y un modelo de intervención del docente para enfrentar la solución de problemas como objeto de enseñanza. ABSTRACT Unstopable (uninterrupted) development of society makes men to plan themselves higher goals every year for their own formation and general development. An important role in the students’ intellectual formation in the development of their mental potentialities and their mathematical preparation in general is the solution of mathematical problems. That is why, it is necessary to introduce methods and new ways that to favor the teaching- learning process of problems solution since the very first grades in the school. This work deals with the principal factors that affect the learning of problems solution, it also offers the basic elements to achieve in different stages of the development of the children, besides it gives a model of teacher`s intervention to face the problems solution as an objective of the teaching process. KEY WORDS: Solution of problem, learning of the solution of problem, levels of development, model of intervention.